PENGARUH ELEMEN-ELEMEN FRAUD PENTAGON TERHADAP KECURANGAN PELAPORAN KEUANGAN BUMN LISTING DI BURSA EFEK INDONESIA TAHUN 2016-2020 - Imam Akram Rizqi; Agus Purwanto (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of the elements contained in the fraud pentagon, namely pressure, opportunity, rationalization, competence, and arrogance on fraudulent financial reporting. Fraudulent financial reporting measured by the F-score. Pressure is proxied by financial targets. Opportunity is proxied by ineffective monitoring. Rationalization is proxied by auditor change. Competence is proxied by change of director. Arrogance is proxied by political connections.The data used in this study are secondary data obtained from the financial statements and annual reports of State-Owned Enterprises listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The number of samples used is 105 samples from 21 companies selected through purposive sampling technique. The data analysis method used in this study is multiple linear regression analysis.The results show that pressure has a positive and significant effect on fraudulent financial reporting. While opportunity, rationalization, competence and arrogance have no effect on fraudulent financial reporting.